PENGARUH JARAK TANAM DAN KOMPOS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BUNGA MATAHARI (Hellianthus annuus L.) PADA LAHAN BEKAS TAMBANG SEMEN - Maryuliyanna Maryuliyanna; Alfandi Alfandi (Agroswagati Jurnal Agronomi, 2017)
This research intends to know the effect of : (1) the interaction effect between treatment plant spacing and the provision of compost on the growth and yield of sunflower (Helianthus annuus L.), (2) a plant spacing (the population) and the dose of the best compost on the growth and yield of sunflower (Helianthus annuus L.), and (3) the effect of the correlation between plant growth and yield of sunflower (Helianthus annuus L.).The experiment was conducted at the area of PT Indocement Tunggal Tbk in Gempol, District palimanan, Cirebon, West Java. The location is situated at an altitude of 11 meters above sea level, average air temperature is 28oC, the type of rain according to Schmidt and Fergusson (1951) includes the type of rain D (moderate). The research was conducted in March until June, 2016.The method used in this research was the experimental method. The experimental design used was a Randomized Block Design (RBD) Factorial. The treatment consists of two factors, plant spacing (J) and compost (K), which consists of four levels. Plant Spacing are J1 (60 cm x 15 cm), J2 (60 cm x 20 cm), J3 (60 cm x 25 cm), and J4 (60 cm x 30 cm). The dose of compost are K1 (0 ton/ha), K2 (10 tons / ha), K3 (20 ton / ha) and K4 (30 tons / ha)).The results showed that there was interaction between plant spacing and compost on growth parameters include components seedling height age of 35 and 49 days after planting, leaf number aged 35 HST, stem diameter ages 35 and 49 days after planting, and root volume age 87 HST and outcome parameters include component diameter flowers, flower weight a plant and a plot and seeds a plant and a plot. At the level of treatment J1K4 (spacing of 60 cm x 15 cm and compost 30 tons / ha) which is 638.92 grams / plot equivalent to 1,775 tons / ha. Then there is a definite correlation between growth (plant height ages 21, 35, and 49 days after planting, leaf number aged 35 and 49 days after planting, area index Leaf (ILD), a trunk diameter of age the age of 21, 35, and 49 days after planting, root volume age 28 and 87 HST) with the results of seed weight a plot.